Orbital Cellulitis: A Rare Presentation of Metastatic Bronchial Carcinoma - Rohit Kumar; Wolfgang Issing (Case Reports in Otolaryngology)
Objective. We report a rare and unusual case of bronchial carcinoma presenting with symptoms of complications of sinonasal disease. Case Report. A 66-year-old lady was referred with a 1-week history of progressive ocular pain, chemosis, and visual disturbance. Computed tomography of the paranasal sinuses revealed frontal and ethmoidal sinus opacification with orbital involvement consistent with a diagnosis of orbital cellulitis secondary to sinusitis. Surgical exploration revealed that the sinuses and right orbit were filled with soft tissue and subsequent histopathological examination of the biopsies indicating metastases from an adenosquamous bronchial carcinoma. Further imaging revealed a large, asymptomatic, bronchial primary with deposits in the brain and liver. The advanced presentation of the disease limited treatment to best supportive care. Conclusion. Orbital cellulitis and sinonasal malignancies have a similar pattern of clinical presentation, posing a potential diagnostic pitfall. There are only two previously reported cases of metastatic lung carcinoma in the frontal sinus with 15 cases of sinonasal tract involvement reported overall. There are no reported cases of adenosquamous carcinoma in the sinonasal tract.